In Silico Analysis of Regulatory Elements of the Vitamin D Receptor (Baghdad Science Journal, 2020)
Vitamin D receptor (VDR) is a nuclear transcription factor that controls gene expression. Its impaired expression was found to be related to different diseases. VDR also acts as a regulator of different pathways including differentiation, inflammation, calcium and phosphate absorption, etc. but there is no sufficient knowledge about the regulation of the gene itself. Therefore, a better understanding of the genetic and epigenetic factors regulating the VDR may facilitate the improvement of strategies for the prevention and treatment of diseases associated with dysregulation of VDR. In the present investigation, a set of databases and methods were used to identify putative functional elements in the VDR locus. Histone modifications, CpG Islands, epigenetic marks at VDR locus were indicated. In addition, repeated sequences, enhancers, insulators, transcription factor binding sites and targets of the VDR gene, as well as protein-protein interactions with bioinformatics tools, were reported. Some of these genetic elements had overlapped with CpG Islands. These results revealed important new insight into the molecular mechanisms of the VDR gene regulation in human cells and tissues.